2016
DOI: 10.1177/1833358316639448
|View full text |Cite
|
Sign up to set email alerts
|

Documentation of clinical care in hospital patients’ medical records

Abstract: On-the-job education with feedback in clinical documentation provides a learning opportunity for medical students and is essential in order to ensure accurate, safe, succinct and timely clinical notes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 25 publications
(30 reference statements)
1
12
0
1
Order By: Relevance
“…Both our findings and prior research suggest that learning composing occurs through trial and error, with inconsistent effort to directly tell trainees where their priorities should be and why (DeLeon et al, 2018;Rowlands et al, 2016). While prior efforts have shown that documentation quality can be improved with feedback (DeLeon et al, 2018;Opila, 1997;Rowlands et al, 2016), we would suggest that using our findings to teach trainees about composing might help them to not only improve documentation quality but also to better understand where they should focus their attention.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Both our findings and prior research suggest that learning composing occurs through trial and error, with inconsistent effort to directly tell trainees where their priorities should be and why (DeLeon et al, 2018;Rowlands et al, 2016). While prior efforts have shown that documentation quality can be improved with feedback (DeLeon et al, 2018;Opila, 1997;Rowlands et al, 2016), we would suggest that using our findings to teach trainees about composing might help them to not only improve documentation quality but also to better understand where they should focus their attention.…”
Section: Discussionmentioning
confidence: 49%
“…These documentation types are a part of trainees’ day to day work across all levels of training, from their time as medical students up to senior residency. To date, clinical documentation research in medical education has largely focused on: problematizing the time spent on it, which at times conflates administrative documentation with other types of documentation (Petrany, 2013 ; Dresselhaus et al, 1998 ; Sinsky et al, 2013 ; van Schaik et al, 2019 );learning how to do it (DeLeon et al, 2018 ; Opila, 1997 ; Rowlands et al, 2016 ); and the importance of doing it well (Cadieux & Goldszmidt, 2017 ; Goldszmidt et al, 2014 ). The potential role it plays in trainee learning and how it changes through their medical education, however, has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Glavne, odnosno prve sestre odjeljenja i zavoda, sastavljaju planove zdravstvene njege, prema utvrđenim potrebama pacijenata za njegom, kao i otpusno sestrinsko pismo [8]. Prednosti elektronskog (informatičkog) programa su [9]: jednostavniji i brži unos informacija, u odnosu na ručni (papirnati) zapis, te je primopredaja smjene mnogo jasnija, sadržajnija i konkretnija. Obavezni dijelovi sestrinske dokumentacije su sestrinska anamneza, sestrinske dijagnoze i informacije o pacijentu čime se omogućava praćenje stanja pacijenta tokom hospitalizacije i trajno praćenje postupaka, tretmani, terapija i dijagnostički postupci, trajno praćenje stanja pacijenta, i naravno plan zdravstvene njege, lista provedenih sestrinskih postupaka, te otpusno pismo zdravstvene njege.…”
Section: Pogled U Budućnost (Elektronski Dokument Medicinske Sestre)unclassified
“…Finally, although becoming proficient in written communication is an expected competency ( 16), many trainees believe they receive insufficient education to become accomplished in clinical documentation (9,17). Although clinical documentation may be thought of as an unnecessary administrative responsibility, it is important for medical students to become proficient in this mode of communication.…”
mentioning
confidence: 99%
“…Although clinical documentation may be thought of as an unnecessary administrative responsibility, it is important for medical students to become proficient in this mode of communication. In spite of this, medical students have noted important barriers to their learning: instruction in oral communication is prioritized over written documentation, trainees who are responsible for teaching more junior staff are not well versed in note writing themselves, and attending physicians fail to read trainee documentation and give formative feedback (17). Additionally, medical students are not always allowed to document in the medical record.…”
mentioning
confidence: 99%